The Effect of Green Accounting and Green Intellectual Capital on Profitability - Meily Surianti; Michelle Theresa Hutagalung; Selfi Afriani Gultom; Anriza Witi Nasution; Cahyoginarti (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
Profitability is the target of this research, which intends to investigate the role of green accounting, green human capital, green structural capital, and green relational capital. Secondary sources, including a 2021to2022 annual report, a sustainability report, and a PROPER rating, provided the data for this study. A total of 31 firms were gathered as study samples via purposive sampling. The tests were conducted using Smart-PLS software and multivariate statistical analysis using the SEM-PLS technique. According to this study's findings, all four types of green capital, green accounting, green human capital, green structural capital, and green relational capital, had no impact on profitability.